2021
DOI: 10.3389/fpsyg.2021.666765
|View full text |Cite
|
Sign up to set email alerts
|

Leader–Follower Congruence in Work Engagement and Leader–Member Exchange: The Moderating Role of Conscientiousness of Followers

Abstract: Extant research has investigated the relationship between work engagement and various outcomes, such as job performance and organizational commitment, neglecting the effect of work engagement on social relationships at work. Drawing upon person-environment fit theory and LMX theory, the present study aims to examine the effect of (in)congruence between leader and follower work engagement on leader–member exchange (LMX) and the moderating effect of conscientiousness. About 273 employees and 72 leaders participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…The results of the present study are also similar to those of Ammon (2013), Beever (2008), andJohnson (2003), who found that the majority of followers report high levels of effective followership. Similarly, Delfino (2019) found that there were high levels of overall active engagement in participants, while Cardwell (2011), andYe et al (2021) found high mean scores for followership and engagement in work. On the other hand, the results of the present study are contradicted by Novikov (2016), who found only a moderate level of followership effectiveness in study subjects Concerning the relationship between toxic leadership and nurse effectiveness, it is notable that there was a statistically significant negative weak correlation between overall toxic leadership and its related dimensions with overall nurse effectiveness and its related dimensions.…”
Section: Discussionmentioning
confidence: 95%
“…The results of the present study are also similar to those of Ammon (2013), Beever (2008), andJohnson (2003), who found that the majority of followers report high levels of effective followership. Similarly, Delfino (2019) found that there were high levels of overall active engagement in participants, while Cardwell (2011), andYe et al (2021) found high mean scores for followership and engagement in work. On the other hand, the results of the present study are contradicted by Novikov (2016), who found only a moderate level of followership effectiveness in study subjects Concerning the relationship between toxic leadership and nurse effectiveness, it is notable that there was a statistically significant negative weak correlation between overall toxic leadership and its related dimensions with overall nurse effectiveness and its related dimensions.…”
Section: Discussionmentioning
confidence: 95%
“…Although several scientific pieces of evidence support the relationship between leadership and work engagement, congruent and simultaneous leader-follower evaluations and their effect on followers' work engagement have not been investigated yet. As far as we know, only Ye et al (2021) examined the leader-follower congruence in work engagement in association with fit theories, but they did not investigate the effect of leadership behaviour on engagement, while Thompson and Glasø (2018) also used joint assessment from leaders and followers in association with situational leadership and follower commitment, but with different theoretical backgrounds. Based on the preliminary findings of Chaudhary (2014); Monica (2019), and Wollard and Shuck (2011), we hypothesised that evaluations based on perceptions affect work engagement, and they could have different impacts in the case of followers' and leaders' evaluations.…”
Section: Discussionmentioning
confidence: 99%